Johann Peter Kirsch und die altrömische Liturgiegeschichte: eine Relecture ausgewählter Studien - Klöckener, Martin (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2025)
"Johann Peter Kirsch and the history of the early Roman liturgy: A re-reading of selected studies" - Johann Peter Kirsch (1861-1941) is best known as a teacher and researcher in early church history and Christian archaeology. However, his field of teaching as a professor at the Faculty of Theology at the University of Fribourg/Switzerland, which he was responsible for until his retirement in 1932, was broader and included the subjects of early church history, patrology, history of dogma, Christian archaeology and, to some extent, liturgical history. Kirsch did indeed regularly teach courses on the history of liturgy, especially of the early church, in German and French, which is discussed in the first section of this article based on the course catalogues. Kirsch also frequently dealt with liturgical history topics in his publications, mainly with reference to Rome; the second section provides an overview of this, points out the thematic cross-connections between publications and teaching and shows his involvement in growing liturgical science networks. In the third section, two selected monographs on the history of the liturgy are analyzed in more detail and questioned as to their lasting significance, firstly the study Der stadtrömische christliche Festkalender im Altertum (1924) and secondly Die Stationskirchen des Missale Romanum (1926), which, despite all the limitations that have emerged after around a century, are still worthy of attention.